Comparative analysis of stakeholder experiences with an online approach to prioritizing patient-centered research topics. (19th December 2016) - Khodyakov, Dmitry; Grant, Sean; Meeker, Daniella; Booth, Marika; Pacheco-Santivanez, Nathaly; Kim, Katherine K
Abstract : Objective: Little evidence exists about effective and scalable methods for meaningful stakeholder engagement in research. We explored patient/caregiver experiences with a high-tech online engagement approach for patient-centered research prioritization, compared their experiences with those of professional stakeholders, and identified factors associated with favorable participant experiences. Methods: We conducted 8 online modified-Delphi (OMD) panels. Panelists participated in 2 rating rounds with a statistical feedback/online discussion round in between. Panels focused on weight management/obesity, heart failure, and Kawasaki disease. We recruited a convenience sample of adults with any of the 3 conditions (or parents/guardians of Kawasaki disease patients), clinicians, and researchers. Measures included self-reported willingness to use OMD again, the panelists' study participation and online discussion experiences, the system's perceived ease of use, and active engagement metrics. Results: Out of 349 panelists, 292 (84%) completed the study. Of those, 46% were patients, 36% were clinicians, and 19% were researchers. In multivariate models, patients were not significantly more actively engaged (Odds ratio (OR) = 1.69, 95% confidence interval (CI), 0.94–3.05) but had more favorable study participation (β = 0.49; P  ≤ .05) and online discussion (β = 0.18; P  ≤ .05) experiences and were more willing to use OMD again (β = 0.36; P  ≤ .05), compared to professional stakeholders. Positive perceptions of the OMD system's ease of use (β = 0.16; P  ≤ .05) and favorable study participation (β = 0.26; P  ≤ .05) and online discussion (β = 0.57; P  ≤ .05) experiences were also associated with increased willingness to use OMD in the future. Active engagement was not associated with online experience indices or willingness to use OMD again. Conclusion: Online approaches to engaging large numbers of stakeholders are a promising and efficient adjunct to in-person meetings.